2001
DOI: 10.1006/jmsc.2000.0999
|View full text |Cite
|
Sign up to set email alerts
|

Survival of decapod crustaceans discarded in the Nephrops fishery of the Clyde Sea area, Scotland

Abstract: The Clyde Sea Nephrops fishery produces large amounts of invertebrate discards. Of these, as much as 89% are decapod crustaceans, including the swimming crab Liocarcinus depurator (Linnaeus, 1758), the squat lobster Munida rugosa (Fabricius, 1775) and the hermit crab Pagurus bernhardus (Linnaeus, 1758). The short-term mortality of these species was assessed following trawling and periods of aerial exposure on deck (16-90 min), and ranged from 2-25%, with Pagurus bernhardus showing the lowest mortality. Two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…In conformity with Bergmann & Moore (2001), individuals were deemed to be dead when no movement of scaphognatite and reaction to external stimulus were observed.…”
Section: Survival Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conformity with Bergmann & Moore (2001), individuals were deemed to be dead when no movement of scaphognatite and reaction to external stimulus were observed.…”
Section: Survival Testsmentioning
confidence: 99%
“…These aspects are reflected, for example, by the pronounced imbalance in terms of damage, physiological stress, and survival among the species subjected to trawling activities. In fact during the fishing process, which includes not only capture by the fishing gear, but also the exposure on deck during commercial catch sorting operations, the individuals may suffer physical damage (Bergmann et al, 2001a;Pranovi et al, 2001) and physiological stress due to thermal shocks and exposure to air (Bergmann et al, 2001b;Gamito & Cabral, 2003) which can lead to high mortality rates (Kaiser & Spencer, 1995;Bergmann & Moore, 2001). Among the discarded species, crustaceans constitute a prominent part of the total biomass and represent an excellent candidate to assess the physical and physiological effects of trawling and sorting procedures (Bergmann et al, 2001b;Pranovi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Clarification of the mating system of Munida species is now of particular relevance not only because of the increasing target fisheries, but also due to the impact from indirect fishing pressures. In western Scotland, for instance, M. rugosa comprises a large component of bycatch from the large-scale commercial Nephrops norvegicus fisheries (Bergmann & Moore 2001). Pothanikat (2005) produced the only report detailing the mating behaviour of Munida sarsi, which was based upon laboratory observations.…”
Section: Introductionmentioning
confidence: 99%
“…Survival studies on Nephrops have reported variable survival rates following capture, air exposure and transport procedures (Ulmestrand et al, 1998;Campos et al, 2015;Bergmann and Moore 2001;Philp et al, 2015), but if post-catch practices are optimised then relatively high survival rates can be achieved, even after trawling (Lund et al, 2009;Albalat et al, 2010). The condition of such animals can nevertheless vary, especially with season (Lund et al, 2009), and for this reason visual methods to assess their condition are important (Stoner, 2012).…”
Section: Discussionmentioning
confidence: 99%